A parallel sweep method for hybrid supercomputers - Bykov, A.N.; Erofeev, A.M.; Sizov, E.A.; Fedorov, A.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2013)
An approach to parallelize the sweep method on hybrid computers using accelerators is considered. The numerical results illustrating the parallelization efficiency of this approach are discussed for the running heat wave problem. The paper was recommended for publication by the Program Committee of the HPC-2012 Forum (http://agora.guru.ru/hpc2012).